Statistical Study on L‐O Mode Saturn Kilometric Radiation - Junhao Pan; Siyuan Wu; Shengyi Ye; Georg Fischer; Laurent Lamy; Philippe Zarka; Ulrich Taubenschuss (Geophysical Research Letters)
Abstract Based on the 13 years‐long observation of Saturn kilometric radiation (SKR) by the Cassini/Radio and Plasma Wave Science instrument, this study derives statistics for left‐hand (L‐O) mode SKR emissions. These emissions span a frequency range from below 10 kHz to approximately 1,000 kHz, with spectral flux densities ranging between 10−24 and 10−18 W/(m2 Hz) consistent with, although fainter than, right‐hand mode SKR. Predominantly observed within 20 Saturn radii, the occurrence rates of L‐O mode SKR exhibit a preference below 20° in latitude, and a local time asymmetry with a higher occurrence rate on the dayside. Occurrence maps indicate that low‐frequency (<100 kHz) L‐O mode SKR may be obstructed by the Enceladus plasma torus due to the higher electron density, while high‐frequency (>100 kHz) emissions can pass through unhindered. Additionally, a substantial proportion of high‐latitude L‐O mode emissions exhibit strong elliptical polarization, contrasting with predominantly circular polarization observed at low latitudes.